2003
DOI: 10.5194/acp-3-1177-2003
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric impact of the 1783–1784 Laki Eruption: Part II Climatic effect of sulphate aerosol

Abstract: Abstract. The long 1783-1784 eruption of Laki in southern Iceland, was one of the first eruptions to have been linked to an observed climate anomaly, having been held responsible for cold temperatures over much of the Northern Hemisphere in the period 1783-1785. Results from the first climate model simulation of the impact of a similar eruption to that of 1783-1784 are presented. Using sulphate aerosol fields produced in a companion chemical transport model simulation by Stevenson et al. (2003), the radiative … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 43 publications
2
67
0
Order By: Relevance
“…The processes leading to El Niño-like anomalies in response to high-latitude eruptions are thus very different from those hypothesized to act in response to tropical eruptions (25,26) and rely on better-understood mechanisms (19,20). Only a few modeling studies (27)(28)(29)(30) have investigated the climate impacts of high-latitude volcanic eruptions, and none has looked at a potential influence on ENSO. Oman et al (29), using an atmospheric model coupled to a mixed-layer ocean, found a weakening of the summer monsoon circulation and precipitation over Africa and Asia in the summer of the eruption, consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The processes leading to El Niño-like anomalies in response to high-latitude eruptions are thus very different from those hypothesized to act in response to tropical eruptions (25,26) and rely on better-understood mechanisms (19,20). Only a few modeling studies (27)(28)(29)(30) have investigated the climate impacts of high-latitude volcanic eruptions, and none has looked at a potential influence on ENSO. Oman et al (29), using an atmospheric model coupled to a mixed-layer ocean, found a weakening of the summer monsoon circulation and precipitation over Africa and Asia in the summer of the eruption, consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleation events detected in the volcanic plume are characterized by J 2 that are four times higher (J 2 ¼ 4.76 AE 2.63 s −1 ) than the average values computed from long-term measurements (2007)(2008)(2009)(2010)(2011) at the station (J 2 ¼ 1.32 AE 0.9 s −1 on 34 comparable events) and 10% higher than the J 2 99th-percentile value (3.66 s −1 calculated on 34 comparable events). After the observations of the presence of H 2 SO 4 and water in volcanic particles during the Pinatubo eruption by Deshler et al (9), the majority of studies used the H 2 SO 4 − H 2 O binary homogeneous nucleation (BHN) theory (6,7,12,19) to estimate the particle formation rates. In the same manner, we can calculate from our data the H 2 SO 4 − H 2 O binary homogeneous nucleation rate J 2;BHN using Yu's procedure (20), which is the closest to the BHN theory (21).…”
Section: New Particle Formation Eventsmentioning
confidence: 99%
“…The sulfur dioxide emitted in large amounts during explosive volcanic eruptions (8) can be oxidized to sulfuric acid, thus many authors suspect that the formed sulfuric acid gives rise to the formation of new secondary particle from binary homogeneous nucleation mechanism (1,(9)(10)(11)(12). Those new particles can then affect the atmospheric radiative balance both directly and indirectly because they can act as cloud condensation nuclei (CCN) (13).…”
mentioning
confidence: 99%
“…The Laki eruption of 1783/1784 suggests that sulphate injection into the lower stratosphere led to dramatic cooling of the lower atmosphere during the winters of 1783 and 1784 [70,89,90] . Curiously, however, the European summer of 1783 was also particularly hot [91] .…”
Section: Sulphur Dioxide and Halogensmentioning
confidence: 99%